Implementation of the Long Short Term Memory Method for the Recommendation of the Final Project Supervisor - Yoga Handoko Agustin; Andi Sanjaya; Wahyu Sindu Prasetya; Fitri Nuraeni (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Education in Indonesia is divided into several levels, starting from elementary, junior high, high school and higher education. Tri dharma of higher education is one of the goals that must be achieved and implemented by all elements in higher education. The core of the Tri dharma of higher education consists of education and teaching, research and development and community service. This research aims to explore Implementation of the long short term memory (LSTM) method for the recommendation of the final project supervisor. The amount of data used in this study amounted to 285 records with 1,035 unique tokens and class 15. The experiment was carried out by changing the epochs in the long short term memory method which amounted to 10, 20, and 50. The results showed that the best model used epochs 50 with a loss value of 21.68% and an accuracy value of 91.74%.